Contempt of Court in Indonesian Criminal Justice System - T. Subarsyah (International Journal of Science and Society, 2020)
Contempt of court is a cutting the edge in this era. This situasion mostly happened when some people insulted the dignity of the court in case of expressing their disatisfaction to the court. Therefore, contempt of court is a part of criminal offense eventhough there are stipulations concerning the issue. However it does not give any detterent effect since the image of the court remains negative in this country. Therefore, with the Contempt of Court Act and stipulations in the Penal Code on the offense classified as contempt of court, it none other is to guard the authority and privilege of the respect of the court that is impartial and the place where people seek justice.